Prosocial behavior motivation of Acheness volunteers in helping tsunami disaster victims - Safrilsyah; Jusoff, Kamaruzaman; Fadhil, Rahmat (Canadian Academy of Oriental and Occidental Culture, 2009)
The purpose of this research is to explore pro-social behavior motivation of Acheness volunteers, who performed humanitarian activities in helping Tsunami victims in Nanggroe Aceh Darussalam, Indonesia. The research was carried out from July 2005 to February 2006. Data were collected from 147 university students in Banda Aceh and Aceh Besar (86 males and 91 females) using two types of questionnaires: (1) Movitavion of Prosocial Behavior Index (MPBI) and Type of Prosocial Behavior Questionnaires (TPBQ), (2) Demographic characteristics for control data, survey and interview. Data were analyzed descriptively and statistical analysis (hypothesis testing) were done using Stepwise Multiple Regression procedure under SPSS/PC Ver.10.00. Results indicated that Pro-social Behavior Motivation of Acheness Volunteers in helping Tsunami victims in Nanggroe Aceh Darussalam is Empathy-Altruism Hypothesis. Based on statistical analysis on 3 models of Pro-social Behavior Motivation (Empathy-Altruism Hypothesis, Negative State Relief Hypothesis and Empathic Joy Hypothesis) with demographic characteristics of respondents (age, educational background, domicile and sex) only motivation of Empathy-Altruism Hypothesis and sex are significantly correlated with pro-social behavior of Acheness volunteers in humanitarian activities and helping Tsunami victims. The respective R-square is 0.059 and 0.137, result of coefficient are 0.521 and 7.830. The dominant types of pro-social behavior of Acheness volunteers in this study are giving and sharing. They helped tsunami victims by psychosocial, counseling, story reading, games, discussion, and charity distributions.